Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - 6.5 Solving Exponential Equations - 6.5 Exercises: 46

Answer

$m = 7$

Work Step by Step

$-4(3)^{m} + 4300 = (3)^{m} - 6635$ $-4(3)^{m} - 1(3)^{m} = -4300 - 6635$ $(-4 - 1)(3)^{m} = -10935$ $-5(3)^{m} = -10935$ $(3)^{m} = 2187$ $(3)^{m} = (3)^{7}$ $m = 7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.